The Epiploplasty does not prevent the formation of post-traumatic liver abscesses - Ruso Martínez, Luis; Rodríguez, Gustavo; Bruno, Gerardo; Carrerou, Luis; Balboa, Oscar (Cirugía del Uruguay, 2001)
The expedient of resorting to the use of the great epiploon (G.E.) for the purpose offilling hepatic cavities of traumatic origin, is a wellknown technique. The rich vascularization and the increase of macrophage flow to the focus are held to be factors preventing the formation of secondary abscesses.